Parental History and Lifestyle Behaviors in Relation to Mortality From Stroke Among Japanese Men and Women: The Japan Collaborative Cohort Study - Eguchi, Eri (Japan Epidemiological Association, 2012)
BACKGROUND: We assessed the impact of parental history of stroke on stroke mortality, as well as the effect modification between lifestyle and stroke mortality, among Japanese. METHODS: In this community-based, prospective cohort study, 22 763 men and 30 928 women aged 40 to 79 years with no history of cardiovascular disease or cancer at baseline (1988–1990) were followed through 2008. We examined the association between parental history of stroke and stroke mortality and estimated the impact of the combination of lifestyle and parental history on stroke mortality in offspring. RESULTS: During a mean follow-up period of 15.9 years, there were 1502 stroke deaths. In both sexes, participants with a parental history of stroke had a higher risk of stroke mortality as compared with those without such a history. The respective multivariable hazard ratio (95% CI) and population attributable fraction were 1.28 (1.10–1.49) and 5.4% in men, 1.22 (1.04–1.43) and 4.3% in women, and 1.25 (1.12–1.40) and 4.8% in all participants, for offspring with a maternal and/or paternal history of stroke. There was an inverse association between healthy-lifestyle score and stroke mortality, irrespective of parental history of stroke. The overall multivariable hazard ratio for the highest (6–8) versus the lowest (0–3) score categories was 0.56 (95% CI, 0.43–0.72) for participants with a maternal and/or paternal history of stroke and 0.44 (0.36–0.53) for those without such a history. CONCLUSIONS: Parental history of stroke was associated with stroke mortality in offspring. The inverse association between healthy lifestyle behaviors and stroke mortality, regardless of parental history, suggests that lifestyle modification is beneficial, even among individuals with a parental history of stroke.